A DESCRIPTIVE STUDY ON TEACHING MEDIA IN ENGLISH CLASS OF JUNIOR HIGH SCHOOL - Bagus Setiyo Budi (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2020)
Media are tools to help the teacher to inform the material more than easier. Based on the research taht was conducted on teaching media and learning activity at the class, the objectives of this research were to describe: 1) media used during teaching and learning process at seventh grade of SMP N 23 Surakarta, Banyu Anyar in 2019/2020 academic year; 2) the problems faced by the teacher in using media during the teaching and learning process at seventh grade of SMP N 23 Surakarta, Banyu Anyar in 2019/2020 academic year. It was a descriptive study on teaching media in English class. To collect the data, observation, interview, questionnaire, and documents were employed. Then, the data were analyzed by using qualitative technique which consisted of three stages : reducing data, presenting the data, and drawing conclusion.The result of the research showed that 1) The media used were LCD projector, books, whiteboard, flashcard, board marker, and laptop. 2) The problem was not found during the teaching and learning process and it was going well. Keyword:Media, Descriptive Study.